Impact of consumption pattern on carbon dioxide emissions in Malaysia - Abdullah Chik, Norlaila (2012)
This thesis is focused on CO2 emissions related to the consumption pattern in Malaysia arising from the remarkable increase in private consumption in the 1990s and 2000s. This is an important issue that could help change household consumption behavior and demand towards more environmental-friendly products because households play an important role in determining the demand for these products corresponding to reduced CO2 emission.